2016
DOI: 10.1051/0004-6361/201527416
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state constraints for the cold dense matter inside neutron stars using the cooling tail method

Abstract: The cooling phase of thermonuclear (type-I) X-ray bursts can be used to constrain the neutron star (NS) compactness by comparing the observed cooling tracks of bursts to accurate theoretical atmosphere model calculations. By applying the so-called cooling tail method, where the information from the whole cooling track is used, we constrain the mass, radius, and distance for three different NSs in low-mass X-ray binaries 4U 1702−429, 4U 1724−307, and SAX J1810.8−260. Care is taken to only use the hard state bur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
174
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(190 citation statements)
references
References 53 publications
15
174
1
Order By: Relevance
“…The DU processes start for M > M DU 1.88 M what corresponds to a central density of n cen 5 n 0 . The radius of the 1.4M NS is about 12 km, agreeing with the analysis of NS data in [67] and with a recent analysis using the cooling tail method [68], see also Ref. [9] and the contribution to this volume [69].…”
Section: Equation Of Statesupporting
confidence: 89%
“…The DU processes start for M > M DU 1.88 M what corresponds to a central density of n cen 5 n 0 . The radius of the 1.4M NS is about 12 km, agreeing with the analysis of NS data in [67] and with a recent analysis using the cooling tail method [68], see also Ref. [9] and the contribution to this volume [69].…”
Section: Equation Of Statesupporting
confidence: 89%
“…Poutanen et al 2014;Nättilä et al 2016). We have observed that the emission level above 40 keV drops by a factor of three during the Xray burst, causing an integrated flux loss of F loss ∼ 3.6 × 10 −10 erg cm −2 s −1 in the 40−200 keV band.…”
Section: Discussionmentioning
confidence: 82%
“…The gray strip represents the mass of the NS PSR J0348 + 0432, M J0348+0432 = 2.01 ± 0.04M [79]. The yellow region indicates the NS mass-radius constraints from model A of Nättilä et al [12]. Besides the LS220 parametrization, only SLy4 and (barely) KDE0v1 and NRAPR satisfy the M max 2 M constraint.…”
Section: -13mentioning
confidence: 99%